Using the blink reflex as measured by electromyogram to assess cranial nerve involvement in people affected by leprosy - Ulvi, H; Yigiter, R; Yoldas, T; Aygul, R; Varoglu, AO; Deniz, O (Int Journal Leprosy, 2004)
Damage to the peripheral nervous system is particularly frequent in leprosy patients. Trigeminal and facial nerves are among the most commonly affected. The aim of our study was to evaluate the efficacy of the blink reflex as a method for diagnosis of cranial nerve involvement in people affected by leprosy. We studied 37 affected people (mean age: 38 yrs, 20 female and 17 male) and 35 age-matched health subjects (mean age: 34 yrs, 20 female and 15 male). Blink reflexes were obtained after unilateral electrical stimulation of the supraorbital nerve for quantitative analysis of 3 responses, early ipsilateral phasic component (R I), late ipsilateral tonic component (R2i), and late contralateral tonic component (R2c). Nerve conduction parameters were studied in all subjects. The latencies of both the ipsilateral early phasic component (R1) and bilateral late tonic components (R2i and R2c) in people affected by leprosy were significantly prolonged compared with the controls. Out of 37 people affected by leprosy, 22 (59%) showed abnormalities R1 latency, 28 (75%) R2i latency and 31 (83%) R2c latency. No correlation was observed between prolonged latencies and duration of the disease. We conclude that blink reflex testing, which can be easily and rapidly performed in an EMG laboratory using standard equipment, can provide useful and objective information for the diagnosis of cranial nerve lesions and for the determination of the degree thereof.